1969
DOI: 10.1097/00006842-196905000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Hypnotic Analgesia and Placebo Response to Experimental Pain

Abstract: The effects of hypnotically induced analgesia and placebo response to "a powerful analgesic drug" were investigated. Highly motivated Ss, who were either very responsive or essentially insusceptible to hypnosis, performed a task which induced ischemic muscle pain. Special procedures and a modified double-blind condition were adopted to establish plausible expectations in both groups that the two treatments effectively reduce pain intensity. Changes in pain threshold and tolerance following hypnotic and placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
83
0
1

Year Published

1975
1975
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(99 citation statements)
references
References 22 publications
13
83
0
1
Order By: Relevance
“…This supports the previous result according to which placebo and hypnosis are different processes of topdown regulation (McGlashan et al, 1969). However, the recent knowledge is insufficient to make assumptions on whether the state of hypnosis can be described as altered consciousness or are the results rather the manifestation of differences in treatment procedures between placebo and hypnosis.…”
Section: Conclusion Summarysupporting
confidence: 87%
See 1 more Smart Citation
“…This supports the previous result according to which placebo and hypnosis are different processes of topdown regulation (McGlashan et al, 1969). However, the recent knowledge is insufficient to make assumptions on whether the state of hypnosis can be described as altered consciousness or are the results rather the manifestation of differences in treatment procedures between placebo and hypnosis.…”
Section: Conclusion Summarysupporting
confidence: 87%
“…However, the research of these two is often done in parallel and their neurobiological relation or even similarity is yet unclear. So far the only known study conducted on both treatments has shown that highly hypnotizable individuals report feeling less pain during hypnosis than during placebo condition (McGlashan, Evans & Orne, 1969). This result implies that the effects of placebo and hypnosis are at least to some extent separate processes.…”
Section: Introductionmentioning
confidence: 94%
“…Indeed, both subjective anxiety (122,231,327) and anxiety-related brain activity (256) have been found to be reduced after placebo administration.…”
Section: B Expectations Of Therapeutic Benefit Play a Key Role In Mamentioning
confidence: 99%
“…Highly hypnotizable research participants and patients are able to hallucinate the absence of pain to some degree, while the other two groups are not (cf. Karlin, Morgan, & Goldstein, 1980;McGlashen, Evans, & Orne, 1969;Raz, 2004). The changes associated with those with low hypnotizability scores (effect size about .5) and most of the effects for moderates (effect size of about .8) can be attributed to the non-specific effects of hypnosis.…”
Section: Hypnosis and The Evidence Base For Evidence-based Psychothementioning
confidence: 99%